APPLICATION OF CONSTRUCTION MONITORING SYSTEMS FOR PROVISION OF SAFE BUILDING USAGE - V. L. Solomakho; D. V. Solomakho; А. S. Volchok (Наука и техника)
The paper proves the necessity to create modern means of technical diagnostics which are based on up-to-date methods and control means ensuring monitoring of construction objects at all stages of their life cycle and true resource forecasting of their safe usage.It has been proposed to consider a system of construction monitoring as a particular case of SCADA-systems which are developed for accumulation and analysis of process data.